MUSIC AS AN INSTRUMENT OF CULTURAL INFLUENCE IN GLOBAL COMMUNICATIONS - Oleksandr ZLOTNYK; Svitlana BORYSOVA; Volodymyr LYTVYNOV; Oleksandr LYTVYNOV; Iryna POLUBOIARYNA (Studia Universitatis Babeş-Bolyai. Musica)
The relevance of the topic is determined by the intensified interest in cultural ways of minimizing tensions in the geopolitical field. The study focuses on the vector of influence of the phenomenon of cultural diplomacy on the formation, development, and strengthening of international relations. A significant part of the article is devoted to the role of musical art in expanding and improving diplomatic cooperation. The study uses analytical and synthetic methods, generalization, comparison, and induction. The article provides a comparative analysis of practical international initiatives in the field of musical diplomacy in selected countries, including Israel and Palestine, the US and Iran, South and North Korea. Critical limiting factors for the development and effectiveness of cultural diplomacy are identified. Key trends in the use of musical art for peace initiatives and the intensification of cultural exchange between countries are determined. Ways to strengthen diplomatic relations and cooperation in the cultural field in the current geopolitical situation are analyzed. The role of cultural diplomacy as a factor in the integration and productive interaction of individual states and their social formations has been proven. The priorities for the promising application of cultural diplomacy, in particular musical art, for resolving existing conflicts and preventing new ones have been substantiated. The significance of innovative models of cultural and artistic interaction in the international arena for enhancing the effectiveness of interregional diplomatic initiatives has been demonstrated. It is proposed that research within the selected subject area should focus on the development and practical testing of new approaches to the development of musical diplomacy.